cDC1 to cDC2: "Everything I do, Ido1 it for you" - Prentzell, Mirja Tamara; Opitz, Christiane (Immunity, 2022)
Distinct dendritic cell (DC) subsets exert specific functions in immune regulation, but their communication with each other has remained elusive. In this issue of Immunity, Gargaro et al. identify the IDO1-Kyn-AHR axis as a metabolic signaling pathway through which conventional DC subsets communicate and induce tolerogenicity.
Gesehen am 04.08.2022